Mitochondrial translocator protein deficiency exacerbates pathology in acute experimental ulcerative colitis - Jimenez, Isabel A.; Stilin, Allison P.; Morohaku, Kanako; Hussein, Mahmoud H.; Koganti, Prasanthi P.; Selvaraj, Vimal (Frontiers in Physiology, 2022)
In human patients and animal models of ulcerative colitis (UC), upregulation of the mitochondrial translocator protein (TSPO) in the colon is consistent with inflammation. Although the molecular function for TSPO remains unclear, it has been investigated as a therapeutic target for ameliorating UC pathology. In this study, we examined the susceptibility of Tspo gene-deleted (Tspo-/-) mice to insults as provided by the dextran sodium sulfate (DSS)-induced acute UC model. Our results show that UC clinical signs and pathology were severely exacerbated in Tspo-/- mice compared to control Tspofl/fl cohorts. Histopathology showed extensive inflammation and epithelial loss in Tspo-/- mice that caused an aggravated disease. Colonic gene expression in UC uncovered an etiology linked to precipitous loss of epithelial integrity and disproportionate mast cell activation assessed by tryptase levels in Tspo-/- colons. Evaluation of baseline homeostatic shifts in Tspo-/- colons revealed gene expression changes noted in elevated epithelial Cdx2, mast cell Cd36 and Mcp6, with general indicators of lower proliferation capacity and elevated mitochondrial fatty acid oxidation. These findings demonstrate that intact physiological TSPO function serves to limit inflammation in acute UC, and provide a systemic basis for investigating TSPO-targeting mechanistic therapeutics.